The Digitalization of MSMEs in Pelawi Utara District, Langkat Regency: Opportunities and Challenges - Ahmad Fadlan; Rizal P. Lubis; Khairul Anwar Sinulingga (Best Journal of Administration and Management, 2023)
This study's goal was to outline the opportunities and challenges of how digitization will affect MSMEs. We combined publication trends from numerous papers using the qualitative methodology to find them. We found that the process of digitizing MSMEs involves switching from analog to digital technologies in order to improve the efficacy and efficiency of MSMEs business operations. The digitization of MSMEs has compelled stakeholders in MSMEs businesses to change corporate governance from outdated techniques to more contemporary ones. For MSMEs, becoming digital involves more than just utilizing technology to sell goods. Additionally, MSMEs will be able to manage their accounts, track their cash flow, and buy raw materials online as a result of digitization. As a result, digitization is crucial to the whole operation of MSMEs business activities.